An updated consecutive modal pushover (UCMP) procedure for estimating the ductility level earthquake design demands of jacket offshore platforms. Issue 145 (June 2021) - Zarrin, Mohamad; Poursha, Mehdi; Gharabaghi, A.R. Mostafa
Abstract: According to API- RP-2EQ/ISO 19901-2:2004(E), the static pushover method is allowed to be utilized for the abnormal level earthquake (ALE) design check of jacket type offshore platforms (JTOP) under the effects of earthquake ground motions. Therefore, the pushover method can be employed to check the ductility adequacy of JTOP structures under ALE (the ductility level earthquake in the previous versions of the API). In this paper, two modifications to the consecutive modal pushover (CMP) procedure are proposed in order to take into account the progressive changes in the dynamic characteristics of JTOP structures as well as the effects of higher modes on the seismic demands of JTOPs. The first modified procedure is called the updated consecutive modal procedure (UCMP), in which the load pattern for the second mode is updated at the beginning of the second stage of the CMP procedure based on the inelastic state of the structure at the end of the first stage. The UCMP procedure conceptually introduces a great advantage over the current enhanced pushover procedures as it considers the change of the dynamic characteristics in the applied load pattern, while it maintains the non-adaptive nature of the CMP method. The second modified procedure, that is called the adaptive-alfa consecutive modal pushover (ACMP) procedure, is proposed to define the displacement increments for the two-stage UCMP procedure based on the instantaneous effective modal participating mass ratio (α). The proposed methods are applied to two case study JTOP models, and the predicted seismic demands are compared with those from the benchmark nonlinear time history (NTH) analyses. A suite of earthquake records, selected based on the ductility level response spectrum, is used for the NTH analysis. The results show that notable improvements are achieved by the UCMP method in estimating the seismic demands of the lower braced stories of the jacket, where the effects of higher modes are expected to be more significant. Therefore, it is recommended to utilize the UCMP method when a trade-off between the accuracy of the pushover analysis and its simplicity is of interest. Moreover, the ACMP method produces an excellent prediction of the seismic demands at the lower stories of the jacket, and provides satisfactory estimations at the foundation part. Consequently, this method is proposed as a rigorous one to be utilized in the design phase of the fixed offshore platforms for the ductility level earthquake check. Highlights: The UCMP procedure is proposed to take into account the progressive changes in the dynamic characteristics of JTOPs. The ACMP procedure is proposed to define the displacement increments of the two-stage analysis in the UCMP procedure. The accuracy of the first mode pushover method is evaluated by comparing with the nonlinear time history analysis. The enhanced pushover analyses are used for the seismic demand evaluation of JTOPs to consider the effect of higher modes.